Inhibitory effects of polyoxyethylene stearate, PANTA, and neutral pH on growth of Mycobacterium genavense in BACTEC primary cultures. - Realini, L (1997)
We report on the influences of polyoxyethylene stearate (POES), PANTA, and pH on primary cultures of Mycobacterium genavense in BACTEC vials. As a model for primary cultures from tissue, seven different strains first isolated from AIDS patients (five from Switzerland and two from the United States) were inoculated into nude mice in order to obtain large amounts of bacilli to test different conditions simultaneously. Our results demonstrate that the size of the inoculum (10[6] acid-fast bacilli/vial), an acid pH (pH 6.0), and the absence of additives (POES and PANTA) significantly (P < 0.001) increased the probability of a successful culture in 1 month, considering growth index (GI) of > or =100 or a GI of > or =999 as criterion of success. In logistic regression analysis, all factors maintained a significant (P < 0.001) independent effect, and no interactions were observed between them. The best conditions for the primary cultures of M. genavense were the use of Middlebrook 7H12 medium at pH 6.0 without any additives.